Spermiogenesis and spermatozoon ultrastructure of Hunterella nodulosa (Cestoda: Caryophyllidea), a monozoic parasite of suckers (Catostomidae) in North America - Yoneva, Aneta; Levron, Celine; Oros, Mikulás; Orosová, Martina; Scholz, Tomás (Folia parasitologica, 2012)
Spermiogenesis and ultrastructure of mature spermatozoon of the caryophyllidean cestode Hunterella nodulosa, a parasite of suckers (Catostomidae), have been studied by transmission electron microscopy. This monozoic tapeworm is unique in its mode of attachment and represents the second North American species studied. The process of spermiogenesis of H. nodulosa follows the general pattern already described in other caryophyllideans. The most characteristic feature is the presence of a slight rotation of the flagellar bud, which seems to be a typical character of spermiogenesis in this cestode group. The mature spermatozoon of H. nodulosa is characterized by the presence of one axoneme of 9 + "1" type of the trepaxonematan flatworms surrounded by a semi-arc of cortical microtubules in its anterior extremity, parallel nucleus and cortical microtubules arranged in a parallel pattern, which corresponds to the Type III pattern of cestode spermatozoa according to Levron et al. (2010). Comparison of the present data with those available for other caryophyllideans did not reveal substantial differences, even though they belong to different families, infect different hosts (catostomid, cyprinid and siluriform fishes) and occur in distant zoogeographical regions. This indicates uniformity of the process of sperm formation and spermatozoon ultrastructure in one of the evolutionarily most ancient groups of tapeworms.
Keywords: Fish Diseases; nemoci ryb; Male; Spermatozoa; spermie; Spermatogenesis; North America; Cestoda; spermatogeneze; Cypriniformes; mužské pohlaví; Animals; zvířata; máloostní; Severní Amerika